High Dose Vitamin D3 Supplementation Is Not Associated With Lower Mortality in Critically Ill Patients: A Meta-Analysis of Randomized Control Trials - Gao, Zhiwei; Xie, Jianfeng; Li, Cong; Liu, Ling; Yang, Yi (Frontiers in Nutrition, 2022)
Background: Vitamin D deficiency is a common condition in critically ill patients. A high dose of vitamin D3 can rapidly restore vitamin D levels. The aim of this meta-analysis was to synthesize the results from up-to-date randomized control trials (RCT) and validate the effect of vitamin D3 in critically ill patients. Study Methods: Several databases, including PubMed, Web of Science, EMBASE, and the Cochrane Central database, were searched up to December 4th, 2020. All RCTs that investigated the use of a high dose of vitamin D3 in critically ill patients and reported mortality data were included in the meta-analysis. The primary outcome was the mortality truncated to day 28 and day 90. Results: A total of 10 RCTs enrolling 2058 patients were finally included. The use of a high dose of vitamin D3 in critically ill patients could not decrease the mortality truncated to day 28 (RR 0.93, 95% CI 0.78 to 1.11, P=0.43) or day 90 (RR 0.91, 95% CI 0.79 to 1.05, P=0.21). A high dose of vitamin D3 could significantly reduce the ventilator days (MD -9.38, 95%CI -13.44 to -5.31, P＜0.001), but there were no statistic difference in length of ICU stay (MD -2.76, 95% CI -6.27 to 0.75, P=0.12) and hospital stay (MD -2.42, 95% CI -6.20 to 1.37, P=0.21). No significant difference was observed in adverse events between the vitamin D3 group and the placebo group. Conclusion: The use of high dose vitamin D3 was not associated with decreased mortality in critically ill patients, but could significantly reduce the ventilator days.